Aktivitas Imunoglobulin M (IgM) Ekstrak Etanol Kulit Buah Kakao (Theobroma cacao L.) terhadap Tikus Putih (Rattus norvegicus) (Journal of Tropical Pharmacy and Chemistry, 2025)
The research of Immunoglobulin M (IgM) activity of Theobroma cacao peel extract has been done to 20 rats. The parameter is agglutination between serum of rats and antigen. Rats were grouped to 4 group, which are group of negative control and 3 groups as experiment groups those given by extract in 250, 500 and 700 mg doses of rats. On the first day was given SDMK 2% by Intraperitonial and after 5 day the serum taken and tested. The data of agglutination then analyzed by Anova. The experiment showed that Theobroma cacao peel extract has activity as immunostimulant in 500 mg doses of rats effective dose.